Tourism, trade and national welfare - Hazari, Bharat; Sgro, Pasquale M. (Amsterdam, netherland Elsevier B. V., 2004)
This is an impressive book that provides unique analysis of tourism within the context of international trade theory. It is based on research on tourism and trade theory which the authors undertook over the decade. Several part of the book have been presented at seminars in different places.
nmn, 09/08/16
Loan
Keywords: Tourism; Trade